Standards of hygiene for ultrasound-guided core cut biopsies of the breast - Heil, Jörg; Fastner, Sarah; Martiny, Heike; Golatta, Michael; Feißt, Manuel; Madjar, Helmut; Bader, Werner; Hahn, Markus (Ultraschall in der Medizin, 2018)
Purpose The aim was to obtain an overview of the hygiene measures undertaken during ultrasound guided core cut biopsies of the breast by experts certified by the German Society for Ultrasound in Medicine in order to derive recommendations for clinical routine, taking into account the available literature and the lack of evidence based guidelines. Materials and Methods A survey was conducted with all members of the levels I to III of the breast ultrasound working group of the German Society for Ultrasound in Medicine. The estimation of the risk of infection after a core cut biopsy of the breast was asked for as well as the hygiene measures undertaken in practice to avoid infection. Results The risk of infection after a core cut biopsy of the breast was estimated to be one per thousand (median value). The most commonly performed hygiene measures were a spray, wipe, spray desinfection (98.1 %) and the use of sterile gloves (54.7 %). Conclusion Due to the very low risk of infection we recommend the routine use of gloves and an adequate skin disinfection. Contact of the transducer or of an unsterile contact medium with the biopsy needle is considered highly unlikely und should be avoided.
Gesehen am 23.10.2019